Human Capital, Market Imperfections, Poverty, and Migration: Evidence from Albania - Etleva Germenji; Johan Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2005)
The most dramatic recent immigration in Europe is the influx of more than 700,000 Albanians, about a quarter of the total Albanian workforce, in the 1990s. The vast majority migrated illegally. This paper analyses the detfirminants of Albanian migration based on a unique representative survey of rural households. The study confirms that migrants are mostly young, male, and single. Regional variations in migration reflect a combination of cultural and economic factors, including migration costs. However, we find that migrants do not come from the poorest rural households. Moreover, education has a positive, albeit non-linear, effect on the likelihood of migration. Migration is negatively related with household access to alternative income sources and reduced financial constraints but positively related with the presence and household's access to migration networks. Policy implications are that aid programs and government initiatives to invest in rural infrastructure and rural education may have mixed effects on migration. A key policy target to reduce migration should be the creation of non-firm rural employment and rural households?access to finance.
Keywords: F22; O52; P20; 330; Albania; migration; rural household; Internationale Wanderung; Ländlicher Raum; Schätzung; Albanien; Logit-Modell